Writing Strategies Used by High-Achieving Students in Academic Writing - Aisyah Indira; Musdalifah Musdalifah; Sri Rosmiana; Asbar Asbar (Universitas Cokroaminoto Palopo, 2025)
Academic writing is a fundamental competency in higher education, requiring students to develop structured arguments, integrate credible sources, and maintain coherence throughout their writing. This study investigates the academic writing strategies employed by high-achieving students, focusing on five key themes: pre-writing strategies, effective use of academic sources, drafting and structuring arguments, revision and self-editing techniques, and time management. Employing a qualitative case study approach, this research was conducted at Universitas Muhammadiyah Enrekang, involving 15 fifth-semester students from the English Education Department who had successfully completed the Academic Writing course with outstanding academic performance. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns in students’ writing strategies. The findings reveal that high-achieving students systematically engage in pre-writing planning, utilize effective citation and paraphrasing techniques, structure their arguments logically and coherently, revise their work through multiple drafts and peer feedback, and employ disciplined time management strategies to optimize their writing process. These results suggest that explicit instruction in academic writing strategies, integrated peer-review practices, and the use of digital writing tools can significantly enhance students' academic writing proficiency. The study provides pedagogical implications for improving academic writing instruction, particularly in English as a Foreign Language (EFL) contexts.